2011
DOI: 10.1002/tox.20703
|View full text |Cite
|
Sign up to set email alerts
|

Fetal adrenal development: Comparing effects of combined exposures to PCB 118 and PCB 153 in a sheep model

Abstract: This study investigated the effects of exposure to the ubiquitous contaminants polychlorinated biphenyls (PCBs) on the fetal adrenal cortex and on plasma cortisol using the domestic sheep (Ovis aries) as a model. Pregnant ewes were intendedly subjected to oral treatment with PCB 153 (98 μg/kg bw/day), PCB 118 (49 μg/kg bw/day) or the vehicle corn oil from mating until euthanasia on gestation day 134 (±0.25 SE). However, because of accidental cross-contamination occurring twice causing a mixed exposure scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The present study is a part of a research program including female and male offspring, and there are several publications that focus on aspects other than the testes. Zimmer et al (2011) found that plasma cortisol concentration and adrenal cortex thickness were significantly reduced. Further, adrenal weight was decreased and plasma ACTH was increased only in the H-118/L-153 group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study is a part of a research program including female and male offspring, and there are several publications that focus on aspects other than the testes. Zimmer et al (2011) found that plasma cortisol concentration and adrenal cortex thickness were significantly reduced. Further, adrenal weight was decreased and plasma ACTH was increased only in the H-118/L-153 group.…”
Section: Discussionmentioning
confidence: 96%
“…The results from the PCB analyses have been published by Zimmer et al (2011) ( Table 1). The mixture exposures led to three distinct exposure scenarios, including a high PCB 153, low PCB 118 exposed group (H-153/L-118), a high PCB 118, low PCB 153 exposed group (H-118/L-153), and a group with considerably lower tissue concentrations of both congeners (L-153/L-118), as determined by PCB concentrations in adipose tissue.…”
Section: Tissue Pcb Concentrationsmentioning
confidence: 99%
“…Eight papers on potential effects of PCDD/Fs and DL‐PCBs in sheep were identified (Annex A.11.1, Table 88 therein). Three of these concerned the same study with sheep treated with PCB‐118 (Gutleb et al., ; Zimmer et al., ; Krogenaes et al., ). There was apparently a cross‐contamination with PCB‐153 and standards were not checked for the presence of more potent DL‐PCBs and PCDD/Fs.…”
Section: Assessmentmentioning
confidence: 99%
“…Treatment of mice with Aroclor 1254 (a commercial PCB mixture) disrupted spermatogenesis, as evidenced by decreased sperm count, testicular dysgenesis, and lowered estradiol levels (Cai et al 2011). Oral treatment with selected PCB congeners also affected growth, adrenal development, and cortisol production in a fetal sheep model (Zimmer et al 2011). Developmental oral exposure to PCB52 or PCB180 induced alterations of the brainstem auditory evoked potentials (Lilienthal et al 2011).…”
Section: Introductionmentioning
confidence: 99%